Mutual learning for reducing tax gaps in V4 countries and Ukraine: Final report - Iakov Frizis; Krzysztof Głowacki; Katerina Hoskova (Center for Social and Economic Research (CASE), 2017)
The paper is a summary of the exchange of knowledge and experience that took place in the course of the project "Mutual Learning for Reducing Tax Gaps in V4 Countries and Ukraine" co-financed by the Visegrad Fund in the years 2016-2017. Five institutions took part in the project: Center for Social and Economic Research (Warsaw, Poland), Center for Social and Economic Research Ukraine (Kiev, Ukraine), INEKO Institute for Economic and Social Reform (Bratislava, Slovak Republic), EUROPEUM Institute for European Policy (Prague, Czech Republic), and Kopint-Tárki Institute for Economic Research (Budapest, Hungary).
Keywords: H26; H60; 330; tax gap; tax evasion; tax avoidance; tax administration; compliance costs; CIT; PIT; VAT; excise; Visegrad; V4; Ukraine